2006
DOI: 10.2174/138161206778743583
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor Signaling Mechanisms Involved in Dendritic Cell Activation: Potential Therapeutic Control of T Cell Polarization

Abstract: Dendritic cells (DCs) represent a bridge between innate and adaptive immunity, being the maturation process dependent on the binding of pathogen-associated molecular patterns (PAMPs) to Toll-Like Receptors (TLRs) expressed on their surface. TLRs associated to adaptor proteins, following binding to PAMPs, are able to skew specific immune responses towards the T helper (h)(1)- or the Th(2)-type according to the antigenic stimulation involved. Of note, other receptors different from TLRs are expressed on DCs whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 88 publications
(153 reference statements)
0
41
0
2
Order By: Relevance
“…TLRs are expressed in the respiratory epithelial cells and many types of immune cells including mast cells, DCs, T cells, B cells, endothelium, fibroblasts, and vascular smooth muscle (20,21). Following PAMPs or DAMPs binding, TLRs or non-TLRs are able to regulate the function of these cells and skew specific immune responses toward the Th1, Th2, Th17 or Tregs phenotype according to the antigenic stimulation involved (22). In the family of TLRs, TLR2 is a unique member that mediates a TH1 response on one hand (23) and TH2-biased response on the other (24).…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are expressed in the respiratory epithelial cells and many types of immune cells including mast cells, DCs, T cells, B cells, endothelium, fibroblasts, and vascular smooth muscle (20,21). Following PAMPs or DAMPs binding, TLRs or non-TLRs are able to regulate the function of these cells and skew specific immune responses toward the Th1, Th2, Th17 or Tregs phenotype according to the antigenic stimulation involved (22). In the family of TLRs, TLR2 is a unique member that mediates a TH1 response on one hand (23) and TH2-biased response on the other (24).…”
Section: Discussionmentioning
confidence: 99%
“…Major targets of most TLR ligands are the myeloid cells, including macrophages and DCs [33][34][35][36]. It has been reported that several distinct TLR ligands are capable of inducing the expression of 1α-hydroxylase in human monocytes and macrophages [13,16].…”
Section: Subcutaneously Administered Tlr Ligands That Induce Increasementioning
confidence: 99%
“…However, the Dectin-1 mAb interfered with the induction of DNA synthesis by Sophy β-glucan in the PBMCs and also prevented the upregulation of IL-8 production by the U937 cells. In general, β-glucans bind to Dectin-1 while interacting with TLRs, especially TLR-2, to activate the MyD88 adaptor (2,13,36,43). As a result, NF-κB is activated to induce the production of the inflammatory cytokines IL-1, IL-6, IL-8, IL-12, IL-18 and TNF-α, and also the expression of co-stimulatory molecules (20).…”
Section: Immunological Actions Of Sophy β-Glucanmentioning
confidence: 99%